Impact of perceived teachers' competence on students' performance: evidence for mediating role of achievement motivation among vocational colleges students' in Malaysia - Omar, Rosmaria; Ahmad, Nor Aniza; Hassan, Siti Aishah; Roslan, Samsilah (Malaysia Association of Research and Education for Educators, 2017)
The purpose of this study was to explore the impact of perceived teachers’ competence on students’ performance mediated by achievement motivation through students’ perception among the vocational colleges students’ in Malaysia. The sample for this study consists of 360 students from 13 selected vocational colleges all around Malaysia. Participants were between the age of 16-18 years old. Instrument for Teachers’ Competency (ITC) and Achievement Motivation Scales (AMS) that have been adapted and adopted from the original version were used to measure the perceived of teachers’ competence and achievement motivation, respectively. The data was analyzed using AMOS version 22.0 through Structural Equation Modeling (SEM) Analysis indicated that perceived of teachers’ competence was predicted the students’ performance and achievement motivation. The model fit was p=.000, RMSEA=.062, GFI=.925, CFI=.954, TLI=.936 and CMIN/df=2.397. Therefore, this study concluded that achievement motivation has a mediation effects on the relationship between teachers’ competence and students’ performance.